Medial Buttress Plating for Humerus Fractures With Unstable Medial Column. Issue 9 (September 2019) - Park, Sam-Guk; Ko, Young-Jin
Abstract : Summary: The purpose of this study was to report surgical tips and techniques on the use of additional medial buttress plate fixation in proximal humeral fractures with unstable medial column restoration after lateral locking compression plate fixation. Between April 2011 and January 2017, 17 patients with medial cortical deficiency were treated using this technique. The average follow-up period was 30 (range, 12–81) months. Successful fracture healing was achieved in all 17 cases. The mean neck-shaft angle change was 1.33 degree (range, 0–7.4 degree). Anterior glenoid rim erosion occurred in 1 patient. No avascular necrosis of the humeral head or significant loss of reduction, and no implant failure or screw perforation occurred. In the first part of this study, we described in detail the indications and surgical technique applied to these fractures. In the second part, we reviewed the clinical and radiographic outcomes of these patients. Supplemental medial buttress plate fixation after lateral locking compression plate fixation was effective in preventing varus collapse and implant failure for proximal humeral fractures with an unstable medial column.